Evidence for 30-40S RNA as Precursor of the 60-70S RNA of Rous Sarcoma Virus - Canaani, E. (National Academy of Sciences, 1973)
Rous sarcoma virus harvested from cells at intervals of 3 min has the same density, sedimentation coefficient, and DNA polymerase as virus harvested at hourly intervals. The RNA of the Prague strain-C consists of a minor class of 60-70S RNA, a major class 30-40S RNA, and a 4-12S class of RNA present at variable concentration. The RNA of the Schmidt-Ruppin strain-A contains more 60-70S than 30-40S RNA. Upon incubation of virus harvested at 3-min intervals at 40° in cell growth medium or Tris-saline, most of the 30-40S RNA is converted to 60-70S RNA. The electrophoretic mobility of the 30-40S RNA of the Rous virus harvested at 3-min intervals is lower than that of the 30-40S subunits of completely dissociated 60-70S RNA; after heating, their mobilities are identical. Heating also releases some small RNAs from 30-40S RNA of virus harvested at 3-min intervals, but five times more 4S RNA is released if the 30-40S RNA is allowed to convert to 60-70S in the virus. The template activity for Rous virus DNA polymerase of the 30-40S RNA of Rous virus harvested at 3-min intervals is about five times lower than that of 60-70S RNA. It is suggested that association of 30-40S RNAs with some RNAs of the 4-12S class may take place simultaneously with their conversion to 60-70S RNA.